Key drivers of automobile brand choice in Jakarta - Hidayatullah, Mochamad Ilham; Hermina, Nurul; Yazid, Mohd Faizun Mohamad (International Journal of Psychosocial Rehabilitation, 2020)
The paper aims to investigate the determinants of automobile brand choice in Indonesia. Specifically, the paper seeks to hypothesize that consumers of automobiles make their purchases based on a multiplicity of factors namely brand image, emotional connection and price. This study was conducted using questionnaires. 212 respondents gathered from selected automobile centers within the province of Indonesia. The data were interpreted using structural equation model in order to measure the hypothesis. The results revealed that brand image and price significant related to brand choice. However, emotion connections did not influence customer towards the brand choice in Indonesia. The result can be used by the car manufacturer, marketing expert and salespeople to plan their advertisements and sales kit in order to closed deal and attract more customers. Further study on the customer decision making is necessary as the action taken by customer may also took into the considerations of the current economy situations and their ability to commit over a long term of time should the purchase was made intentionally through hire purchase scheme.